2018
DOI: 10.1164/rccm.201709-1807oc
|View full text |Cite
|
Sign up to set email alerts
|

Intensified Therapy with Inhaled Corticosteroids and Long-Acting β2-Agonists at the Onset of Upper Respiratory Tract Infection to Prevent Chronic Obstructive Pulmonary Disease Exacerbations. A Multicenter, Randomized, Double-Blind, Placebo-controlled Trial

Abstract: Intensified combination therapy with ICS/LABA for 10 days at URTI onset did not decrease the incidence of any COPD exacerbation but prevented severe exacerbation. Patients with more severe disease had a significant risk reduction for any exacerbation. Clinical trial registered with www.isrctn.com (ISRCTN45572998).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 41 publications
0
38
0
2
Order By: Relevance
“…Inhaled corticosteroids (ICSs) are effective in reducing airway inflammation, nonspecific airway hyperresponsiveness, and airway obstruction in patients with COPD [ 4 ]. An ICS combined with a long-acting β 2 agonist (LABA) is more effective than monotherapy in improving lung function, reducing symptoms, increasing exercise tolerance, decreasing the frequency of exacerbation and hospitalization, and improving patient health [ 5 ]. According to the current Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines, ICSs in combination with LABAs are suggested for patients with moderate-to-very severe COPD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inhaled corticosteroids (ICSs) are effective in reducing airway inflammation, nonspecific airway hyperresponsiveness, and airway obstruction in patients with COPD [ 4 ]. An ICS combined with a long-acting β 2 agonist (LABA) is more effective than monotherapy in improving lung function, reducing symptoms, increasing exercise tolerance, decreasing the frequency of exacerbation and hospitalization, and improving patient health [ 5 ]. According to the current Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines, ICSs in combination with LABAs are suggested for patients with moderate-to-very severe COPD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Τhe PREVENT study [27] is an investigator-initiated and -driven study compiled to the Declaration of Helsinki and Good Clinical Practice Guidelines. The study was approved by the responsible ethics committee (EKNZ 306/10) and was registered at www.controlledtrials.com (identifier ISRCTN 45572998).…”
Section: Methodsmentioning
confidence: 99%
“…(Ding et al, 2016) Intensified combination therapy with ICS/LABA for 10 days at URTI onset could be associated with a reduction of exacerbations, particularly in patients with severe disease. (Stolz et al, 2018) In a recent RCT, the addition of doxycycline to oral corticosteroid an outpatient setting did not prolong time to next exacerbation. (van Velzen et al, 2017) A small pilot RCT (n = 29) reported that six weeks of high-flow nasal cannula oxygen therapy reduced hypercapnia and improved health-related quality of life in patients with stable hypercapnic COPD.…”
Section: Chaptermentioning
confidence: 95%